Benign Structures Mimicking Right Atrial Masses on Prenatal Ultrasound - Snigdha Bhatia; Amna Qasim; Amyn K. Jiwani; Ashraf M. Aly (Case Reports in Pediatrics)
Advances in imaging have resulted in more frequent reporting of primitive right atrial structures which can sometimes mimic cardiac tumors in prenatal ultrasound. Prominent crista terminalis and Chiari network are examples of these structures. We describe two cases of pregnant women referred to the fetal cardiology clinic for fetal echocardiography for right atrial masses seen on prenatal ultrasound suspicious of tuberous sclerosis. The first case subsequently diagnosed as crista terminalis and the second case as a prominent Chiari network. Postnatal ECHO confirmed the benign nature of these structures. It is important to differentiate tumors from prominent benign structures in the right atrium in fetal ECHO. The location and the similar echogenicity to the adjacent atrial tissue are clues for differentiation of these structures from atrial tumors.